Sourcing Patterns of Foreign-owned Multinational Subsidiaries in Europe - Ana Teresa Tavares; Stephen Young (European Regional Science Association (ERSA), 2004)
The paper investigates the determinants of the sourcing patterns of foreign-owned multinational subsidiaries in a cross-country European setting. Sourcing decisions (namely, buying locally versus internationally) represent a highly relevant theme for regional and national host economies, given the potential impact these decisions can have on indigenous industrial systems. The subject under analysis attracts considerable attention in regional economics, given the importance of multinationals' local linkages in generating externalities and technology spillovers and in supporting industrial agglomeration. Additionally, a concern with growing import levels exists, since the globalization of supply chains is creating major competitive pressures for local suppliers, as companies explore global sourcing options. Inter-firm linkages between multinationals and host country suppliers are investigated. The paper is structured as follows: firstly, a thorough literature review on local sourcing, spillovers and regional impact of multinational enterprises is offered. Then, the paper puts forward a general framework of the factors influencing the choice between international and local sourcing, and formulates hypotheses (based on that conceptual framework), on subsidiary roles/characteristics (such as subsidiary age, whether subsidiary was established before or after host country EU integration, entry mode, subsidiary size) and country (home and host) and industry characteristics. Subsequently, an econometric analysis of the main determinants of sourcing decisions is conducted. The empirical setting is multi-country, EU-based. Data result from a large-scale survey of the main foreign-owned subsidiaries in four EU countries (Ireland, Portugal, Spain and the UK). The main contributions of the paper lie in an improved understanding of the influence of foreign-owned subsidiary strategies and economic integration in sourcing patterns, topics on which little research exists. Important conclusions are drawn on the scope to increase local sourcing through policy intervention at national and regional levels. Major findings concern the impact of subsidiary roles and economic integration on sourcing patterns. Regional and global integration are leading to a greater import-orientation among MNE subsidiaries, including high value-added Product Mandate subsidiaries which are assumed to be strongly embedded within host economies.It was found that economic integration (along with age of subsidiary) has a significant impact on sourcing patterns, meaning that subsidiaries established after their host countries' EU accession are less embedded via sourcing; and that subsidiaries in global industries buy less locally, as well as subsidiaries located in small EU economies (that have lower supplying capabilities as the local industry is less diversified). Our results did not find a significant association of subsidiary size, home country and entry mode with the import propensity of the multinational subsidiaries surveyed. This research confirms the significant body of evidence that multinationals have seldom developed extensive input linkages with their host economy, and strengthens the conclusion of previous authors that the potential for local linkages is now significantly reduced as compared with the past. The results cast serious doubts on the effectiveness of traditional criteria for investment attraction; and confirm that stimulating local sourcing is problematic. Specific policy implications are developed relating to the attraction of inward foreign direct investment and to corporate development policies.
Keywords: 330